2020
DOI: 10.1021/acs.langmuir.0c02466
|View full text |Cite
|
Sign up to set email alerts
|

Size Tuned Synthesis of FeOOH Nanorods toward Self-Assembled Nanoarchitectonics

Abstract: Various studies were performed to fabricate self-assembling nanoobjects out of noble metals, but a few efforts were made for engineering iron-based nanorods toward sell-assembling blocks. In this regard β-FeOOH nanorods were fabricated in various sizes to achieve iron-based rod nanoblocks with selfassembling potential. Hydrolysis of ferric ions in various concentrations was successfully developed as a novel approach to control the growth of β-FeOOH crystals and tuning the length of rods in the nano range, belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…As indicated in previous literature, the concentration of ferric salts plays a defining role in the synthesis of β-FeOOH NPs by controlling the growth of nanocrystals. Increasing the concentration of ferric ions leads to an increase in the length of NRs without significant width change and subsequently elevated aspect ratio since a higher concentration of ferric salts provides more ferric precursor along with more acidic pH, facilitating parameters in the hydrolysis process and further growth of NRs [28,33]. In this regard, we also found that increasing the concentration of ferric ions raises the length of NRs without a significant change in aspect ratio (Table 1).…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…As indicated in previous literature, the concentration of ferric salts plays a defining role in the synthesis of β-FeOOH NPs by controlling the growth of nanocrystals. Increasing the concentration of ferric ions leads to an increase in the length of NRs without significant width change and subsequently elevated aspect ratio since a higher concentration of ferric salts provides more ferric precursor along with more acidic pH, facilitating parameters in the hydrolysis process and further growth of NRs [28,33]. In this regard, we also found that increasing the concentration of ferric ions raises the length of NRs without a significant change in aspect ratio (Table 1).…”
Section: Resultssupporting
confidence: 51%
“…FeO 6 octahedral units of β-FeOOH NRs are identified by characteristic peaks of two prominent vibration bands, FeO and OH groups. The vibration of FeO groups of octahedral units was observed as Fe−O bending vibrations at about 400 cm -1 and Fe−O stretching vibrations containing symmetrical stretching bands from 435 to 495 cm -1 and asymmetrical stretching bands at 647 to 700 cm -1 [28,38,39]. As shown in Figure 4, the characteristic absorption peaks related to Fe−O bands of octahedral sites are perceptible between 400 and 700 cm -1 in all sample graphs.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…in the XRD pattern of CuHCF/f-CNT, and are assigned to the tetragonal b-Fe-OOH phase formed due to the reductive environment provided by the PVP in the composite formation. 36 A slightly right shi of peaks can also be observed in the XRD pattern of CuHCF/f-CNT when compared to that of pristine CuHCF, which causes lattice shrinkage due to alkali ion removal from the lattice. 37,38 Besides, an extra peak around 17.7 (marked by #), which indicates a minor phase transformation of the cubic lattice (a…”
Section: Physico-chemical Characterisationmentioning
confidence: 94%
“…Functional material systems are supposed to be nanoarchitected from these nanoscale units upon the selection and combination of various unit processes including atomic/molecular manipulation, chemical/material conversion, self-assembly/self-organization, field-assisted arrangement, nano/micro fabrication, and biochemical/biological treatment [ 48 ]. Since the basic concept of nanoarchitectonics is very general, it can be widely applied to fundamental subjects such as material synthesis [ 49 , 50 , 51 ] and structure control [ 52 , 53 , 54 ], as well as to applied fields such as energy [ 55 , 56 , 57 ], the environment [ 58 , 59 , 60 ], catalysts [ 61 , 62 , 63 ], sensors [ 64 , 65 , 66 ], and devices [ 67 , 68 , 69 ].…”
Section: Introductionmentioning
confidence: 99%